Implementation of Reverse Evidence of Internal Assets Case of Consolidation of Corruption Crimes - Pandri Zulfikar; Rosmalily Binti Salleh (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2023)
The purpose of this study is to find the justification for judicial practice in confiscating the assets of the Defendant who has not been charged with a system of reverse evidence in the combination of Corruption Crimes and Money Laundering Crimes. To find out the application of the Reverse Evidence system regarding the assets of the Defendant who have not been indicted in the case of the merger of Corruption Crimes and Money Laundering Crimes. Qualitative research methods explain the phenomena that occur and prioritize the substance of these phenomena. Techniques for collecting data are interviews with those related to Corruption, observations at research locations, documentation studies in the form of archives, and data according to facts. Conclusion: (1). In implementing Articles 37 and 37.A in Law no.31 of 1999 in conjunction with Law no.20 of 2001, which relates to the Eradication of Corruption Crimes. (2). In Article 38.B paragraph (1) of Law no. 31 of 1999 in conjunction with Law no. 20 of 2001 relating to the Eradication of Criminal Acts of Corruption (3). Article 77 Law no. 8 of 2010 concerning Prevention and Eradication of Money Laundering Crimes. (4). Article 78 of Law no. 8 of 2010, regarding the Prevention and Eradication of Money Laundering Crimes.